Optimal design of dome structures with recently developed algorithm: Rao series. (August 2022) - Dede, Tayfun; Atmaca, Barbaros; Grzywinski, Maksym; Venkata Rao, Ravipudi
Abstract: The modal parameters such as natural frequencies and mode shapes of structures are vital parameters that must be within the certain limits to ensure the desired structural behavior. Optimization of any type of structures regarding natural frequencies as constraints is considered as highly nonlinear and reaching the global solutions is very difficult. Furthermore, optimum design of small, medium and large-scale domes is known as a complicated optimization problem. In this study, the size optimization of the small, medium and large-scale truss dome structures subjected to multiple dynamic frequency constraints by using newly developed meta -heuristic algorithms named Rao algorithms (Rao-1, Rao-2 and Rao-3) is presented. The cross-sectional areas for the truss bar members of dome structures and first five natural frequencies are considered as the design variables and multiple dynamic constraints, respectively. To perform the optimization process of dome structures, a visual computer program is created in Matlab–GUI (Graphical User Interface). This program has combined the Rao algorithms and the finite element analysis using Eigen values of the stiffness matrix. Three different sizes such as small, medium and large-scale dome are examined to show the performance of the Rao algorithms. The examples for the small, medium and large-scale domes contain 120 bar, 600 bar, 1180 bar and1410 bar dome structures. The obtained near-optimal results are compared with the available results found in the literature to indicate the performance of the Rao algorithms. At the end of the study, it is concluded that the Rao algorithms performed similar to other methods and even better in some cases for designing the dome structures. Furthermore, Rao-2 algorithm has achieved the best results in the least number of generations compared to the Rao-1 algorithm.